In vitro Cultured Meat: Nutritional Aspects for the Health and Safety of Future Foods - Chotelersak, Kruawan; Teerawongsuwan, Sasipat; Suwan, Natthima; Saipin, Nungnuch; Jaisin, Yamaratee; Suriyut, Janyaruk; Boonprom, Pattanapong; Dorn-in, Samart; Rungsiwiwut, Ruttachuk (Trends in Sciences, 2024)
In vitro cultured meat is one of the future foods that might revolutionize meat production by allowing food manufacturers to sidestep traditional animal farming. Despite being in early development, in vitro cultured meat faces challenges such as technological limitations and consumer acceptance, hindering its market integration. Beyond being an ethical alternative to conventional meat, it resembles conventionally farmed meat, making it a focus on healthcare and food safety. From a health perspective, it theoretically presents intriguing possibilities in the fields of functional foods, tailored dietary therapy, and public health. In functional foods, its unique composition allows precise nutritional manipulation for specific dietary needs, aligning with personalized nutrition. In dietary therapy, in vitro cultured meat might offer customization for individuals with dietary restrictions or health conditions, providing a novel therapeutic avenue. From a public health standpoint, it holds promise in mitigating environmental and health challenges linked to conventional meat production, aligning with sustainability and disease prevention initiatives. However, the potential health risks of in vitro cultured meat include concerns about the use of genetically modified starting cells, fetal bovine serum, growth factors, scaffolding materials, and antibiotics during the production process. These additives may have unforeseen long-term health effects if not properly regulated. Additionally, in vitro cultured meat may lack some of the natural nutrients found in conventional meat, which could lead to nutritional imbalances. There are also uncertainties about how the texture and bioavailability of nutrients in in vitro cultured meat might affect digestion and absorption in the human body. Nevertheless, specific aspects of research in the field of in vitro cultured meat demand increased focus from researchers to guarantee the optimal safety standards. An in-depth study on safety-oriented research of in vitro cultured meat should be emphasized to ensure benefits for individual and public health. HIGHLIGHTS In theory, in vitro cultured meat offers potential as a novel solution for developing functional foods by allowing precise manipulation of nutritional content, enabling the creation of health-optimized products. In vitro cultured meat could help mitigate the risk of antimicrobial resistance by minimizing the need for antimicrobial agents, reducing overall exposure and the potential for the development and spread of antimicrobial-resistant microorganisms. Starting cells derived from genetically modified cells in the in vitro cultured meat may pose risks of allergenicity and contamination, as well as potential immune responses to novel proteins. Strict safety protocols and thorough testing are crucial to address these risks and ensure the final product is safe for consumption. GRAPHICAL ABSTRACT